Effect of fiber orientation on the shear behavior of glass fiber/epoxy composites - Almeida, Jose Humberto S.; Angrizani, Clarissa C.; Botelho, Edson C. [UNESP]; Amico, Sandro C. (Elsevier B.V., 2015)
This paper deals with the study of the influence of the lay-up configuration on interlaminar and in-plane shear properties of glass fiber reinforced epoxy composites. The following laminates were produced by resin transfer molding with vacuum assistance for this study: [0](5), [90](5), [0/90/0/90/0] and randomly oriented (mat). The composites, with similar overall fiber volume fraction, were evaluated based on four tests: double-notched shear, short beam shear, V-notched rail and Iosipescu shear tests. Besides, the dynamic shear modulus was measured with non-destructive testing based on free vibration method. The [0](5) laminate presented interlaminar shear strength almost twice that of [90](5), whereas the mat samples presented higher in-plane shear strength in both tests used due to its random fiber orientation. The dynamic shear modulus was higher for the composites [0](5), as expected due to the longitudinally oriented fibers. Among the shear test methods applied, double-notched and V-notched methods exhibited more auspicious features, possibly due to a more uniform shear stress state during testing. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: In-plane shear; Interlaminar shear; Non-destructive testing; Laminate; Fabric; Failure mode